2013
DOI: 10.1038/cddis.2013.406
|View full text |Cite
|
Sign up to set email alerts
|

Panobinostat synergizes with zoledronic acid in prostate cancer and multiple myeloma models by increasing ROS and modulating mevalonate and p38-MAPK pathways

Abstract: Patients with advanced prostate cancer (PCa) and multiple myeloma (MM) have limited long-term responses to available therapies. The histone deacetylase inhibitor panobinostat has shown significant preclinical and clinical anticancer activity in both hematological and solid malignancies and is currently in phase III trials for relapsed MM. Bisphosphonates (BPs), such as zoledronic acid (ZOL), inhibit osteoclast-mediated bone resorption and are indicated for the treatment of bone metastasis. BPs, including ZOL, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 43 publications
1
42
1
Order By: Relevance
“…However, SAHA did not affect the phosphorylation of p38 MAPK or JNK1, suggesting that these two MAPKs are not involved in the anti‐fibrotic mechanisms of SAHA in the cornea. These results conflict with those of previous studies which demonstrated the ability of HDACi, including SAHA, to inhibit phosphorylation of p38 MAPK in neoplastic cells, rheumatoid arthritis synovial fibroblast, and lens epithelial cells . It is important to note that these studies utilized cytokines different than TGF‐β1 to induce cellular transformation and fibrosis.…”
Section: Discussioncontrasting
confidence: 71%
“…However, SAHA did not affect the phosphorylation of p38 MAPK or JNK1, suggesting that these two MAPKs are not involved in the anti‐fibrotic mechanisms of SAHA in the cornea. These results conflict with those of previous studies which demonstrated the ability of HDACi, including SAHA, to inhibit phosphorylation of p38 MAPK in neoplastic cells, rheumatoid arthritis synovial fibroblast, and lens epithelial cells . It is important to note that these studies utilized cytokines different than TGF‐β1 to induce cellular transformation and fibrosis.…”
Section: Discussioncontrasting
confidence: 71%
“…LBH589 has been recently approved for treatment of patients with relapsed and refractory multiple myeloma [80]. Although several mechanisms have been proposed for LBH589-dependent generation of ROS [93-95], it is worth noting that KLF9 has been reported by us previously to mediate LBH589 cytotoxicity in multiple myeloma cells [81] and thus could account, at least in part, for the LBH-dependent oxidative stress in these cells. Several other histone deacetylase inhibitors cooperated or synergized with BTZ in inducing oxidative stress and apoptosis in multiple myeloma cells in vitro , including sodium butyrate and suberoylanilide hydroxamic acid [95], PXD101 (belinostat, Beleodaq), [96], and KD5170 [97].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…The MAPK signaling pathway plays important roles in regulating apoptosis induced by various cellular stresses and chemotherapeutic agents [34,35]. However, the detailed mechanisms of these pathways in cell death remain elusive.…”
Section: Allicin Inhibits Sk-n-sh Cell Proliferation and Induces Apopmentioning
confidence: 99%